1985
DOI: 10.2307/3576574
|View full text |Cite
|
Sign up to set email alerts
|

16, 16-Dimethyl Prostaglandin E 2 Induces Radioprotection in Murine Intestinal and Hematopoietic Stem Cells

Abstract: Exogenous prostaglandins (PGs) have been shown to protect gastrointestinal mucosa, liver, and pancreas from several injurious agents, including the PG inhibitor, indomethacin. Previous studies from this laboratory showed exogenous administration of 16,16-dimethyl (dm) PGE2 also protected mouse intestinal stem cells from radiation injury. The present study extended that observation and demonstrated that PGs given to B6D2F1 mice 1 hr before irradiation increased the shoulder of the intestinal clonogenic cell sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(35 citation statements)
references
References 19 publications
3
32
0
Order By: Relevance
“…Prostaglandin E 2 (PGE 2 ), generated from arachidonic acid by cyclooxygenase 1 (COX-1) or COX-2, protects the intestinal epithelium from IR by increasing stem cell survival and diminishing apoptosis (4,5). COX-1 is constitutively expressed and promotes tissue homeostasis.…”
mentioning
confidence: 99%
“…Prostaglandin E 2 (PGE 2 ), generated from arachidonic acid by cyclooxygenase 1 (COX-1) or COX-2, protects the intestinal epithelium from IR by increasing stem cell survival and diminishing apoptosis (4,5). COX-1 is constitutively expressed and promotes tissue homeostasis.…”
mentioning
confidence: 99%
“…In order to resolve whether GLA might act as a radioprotector rather than a BRM these oils were given either up to the time of irradiation only or both before and after irradiation. PGs have been reported to protect against radiation damage (Hanson & Ainsworth, 1985). EFA administration was initiated 4 weeks prior to irradiation to ensure stable EFA levels in the animals before local skin irradiation.…”
mentioning
confidence: 99%
“…Initially it was proposed that the augmentation of radioresponse induced by indomethacin could be due to lowering PGs in tumour tissues. The effects of PGs on radioprotection are, however, not clear: some authors reported that PGs might act as radioprotectors (Hanson & Ainsworth, 1985;Walden et al, 1987), whereas others (Milas et al, 1990) proposed an opposite effect.…”
Section: Radiothinlayer Chromatographymentioning
confidence: 96%
“…Apart from the fact that the mechanisms by which indomethacin potentiates tumour radioresponse are still unclear to date, it appears that an increased tumour response might be achieved by lowering PGs in the tumour. This, however, would imply that PGs are not radioprotective agents as has been suggested by Hanson & Ainsworth (1985) or Walden et al (1987). Milas and coworkers (1990) have also found that potentiation of the tumour radioresponse induced by indomethacin is more significant when it is given after rather than before irradiation.…”
mentioning
confidence: 89%